State and investment opportunities of the population in the financial market of Ukraine - Yakusheva, Inna; Якушева, Інна Євгенівна; Якушева, Инна Евгеньевна (My University, 2020)
The financial market of Ukraine operates in conditions of low investment activity of the population. Investment activity of the population in the financial market is a multifactorial category that reflects the ability and desire of entities to invest in financial instruments in order to save capitalize and generate income. The key forms of accumulation of money and formation of private savings by citizens of our country today are: storage of savings in the form of cash (in national and foreign currency); opening a deposit in banking institutions; formation of a portfolio of securities; consumption of investment services of financial institutions outside the banking system.
Keywords: financial market; income